The context in which we examine disasters in New Zealand: An editorial - O'Connor F; Johnston DM; Evans IM (The New Zealand Psychological Society, 2011)
This is a tale of two earthquakes (you could say many more on account of persistent aftershocks) that were, in a Dickensian way, the best of times and the worst of times. It is a tale of two cities as well. There are a lot of contrasts between the east and the west of the city, and between the two events, as well as lots of comparisons.